A Study on the Experience of Expatriates in India - Bhandari, Geetika (2007)
The purpose of this dissertation was to conduct a research into the experience expatriates have while living and working in India. A comprehensive literature review highlighted that due to globalisation, the international organization has expanded and their scope has even widened in India. It also revealed the importance of expatriation for an individual who takes up such a decision of becoming an international staff. The career opportunities faced by him and the compensation which he receives as a reward of taking up such a difficult task. Moreover, the international assignment has numerous challenges which are associated with it. One of the biggest challenges is the problems they face at a personal and corporate level. While much of the research has been carried out into the expatriation experience in the west it was discovered that little research has been carried out in the developing countries. To investigate further, expatriates in India were interviewed. A semi structured interview was conducted in order to elicit their experiences and their views on how organizations can help in making the experience even better. Further studies were carried out to discover that the experience expatriates gained in India was not very different to any other destination they would be relocated to. Moreover the findings from the research also matched quiet closely with those mentioned in the literature review. This study provided strong evidence to suggest that there should be further research in this field.